People and places - "Rist, Dominique" (Kingfisher, London, 1994)
Focusing on people and places, this is part of a 12-volume encyclopaedia which aims to reflect the concerns of the National Curriculum. The book looks at the distinctive characteristics and daily life of communities in different countries.